Correlation between Global Rating Scale and Specific Checklist Scores for Professional Behaviour of Physical Therapy Students in Practical Examinations. (17th September 2014) - Turner, Kaitlin; Bell, Maegan; Bays, Lindsay; Lau, Carmen; Lai, Clara; Kendzerska, Tetyana; Evans, Cathy; Davies, Robyn
Abstract : The purpose of this study was to determine whether or not the specific item checklist (checklist) and global rating scale (GRS) scores are correlated in practical skills examinations (PSEs). Professional behaviour was evaluated using both the checklist and GRS scores for 183 students in three PSEs. Mean, standard deviation, and correlation for checklist and GRS scores were calculated for each station, within each PSE. Pass rate for checklist and GRS was determined for each PSE, as well as for each individual checklist item within each PSE. Overall, pass rate was high for both checklist and GRS evaluations of professional behaviour in all PSEs. Generally, mean scores for the checklist and GRS were high, with low standard deviations, resulting in low data variability. Spearman correlation between total checklist and GRS scores was statistically significant for two out of five stations in PSE 1, five out of six stations in PSE 2, and three out of four stations in PSE 3. The GRS is comparable to the checklist for evaluation of professional behaviour in physical therapy (PT) students. The correlation between the checklist and GRS appears to become stronger in the assessment of more advanced students.